2019
DOI: 10.21273/hortsci13482-18
|View full text |Cite
|
Sign up to set email alerts
|

Hibiscus Leaf Tissue Nutrient Sufficiency Ranges by Chronological Age

Abstract: Perennial hibiscus (Hibiscus sp.) are popular summer-flowering plants that are grown in greenhouses or nurseries, where growers must optimize production inputs such as fertility to maximize plant growth and produce high-quality flowering crops. The objective of this study was to determine the optimum fertilizer concentrations, identify leaf tissue nutrient sufficiency ranges by chronological age, and to expand leaf tissue nutrient standards of Hibiscus hybrid L. (hibiscus) grown in soilless substrates during c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 7 publications
4
15
0
Order By: Relevance
“…Additionally, average substrate pH decreased by 19% (1.1 pH units), from 5.8 to 4.7 pH units, as fertilizer concentration increased from 50 to 400 mg • L -1 N, respectively. Therefore, based on these results and visual observations, it was concluded that plants fertilized with $100 mg • L -1 N were entering a situation of luxury to detrimental nutrient consumption, and the additional fertilizer was not beneficial to plant quality (Jeong et al, 2009;Krug et al, 2010;Owen, 2019;Papineau and Krug, 2014). When plant growth and substrate pH and EC data are taken together, 75 mg • L -1 N was determined to be the upper nutritional range limit, and plants fertilized with 100 to 400 mg • L -1 N were excluded from further statistical analyses.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Additionally, average substrate pH decreased by 19% (1.1 pH units), from 5.8 to 4.7 pH units, as fertilizer concentration increased from 50 to 400 mg • L -1 N, respectively. Therefore, based on these results and visual observations, it was concluded that plants fertilized with $100 mg • L -1 N were entering a situation of luxury to detrimental nutrient consumption, and the additional fertilizer was not beneficial to plant quality (Jeong et al, 2009;Krug et al, 2010;Owen, 2019;Papineau and Krug, 2014). When plant growth and substrate pH and EC data are taken together, 75 mg • L -1 N was determined to be the upper nutritional range limit, and plants fertilized with 100 to 400 mg • L -1 N were excluded from further statistical analyses.…”
Section: Resultsmentioning
confidence: 96%
“…The increasing con-sumer demand for this herbaceous perennial is because of their colorful foliage and venation; mounding growth habit; use in mixed combination containers or landscape plantings; use as pollinator plants and cut flowers; and their drought-and deer-resistance. To continue to meet the increasing consumer demand for coral bells, greenhouse and nursery growers must optimize production inputs (Owen, 2019), such as fertilization. Traditionally, commercial mineral nutrition recommendations for the genera Heuchera range from 50 to 250 mg • L -1 nitrogen (N) on a continual basis (Biernbaum and Morrison, 2000;Pilon, 2006) or 150 to 200 mg • L -1 N as needed (Nau, 2011;Pilon, 2006).…”
mentioning
confidence: 99%
See 3 more Smart Citations